Case Report: Brentuximab Vedotin Associated Acute Pancreatitis in a Pediatric Hodgkin Lymphoma Patient: Case Report and Literature Review - Ewelina Truszkowska; Marta Andrzejewska; Cyntia Szymańska; Agnieszka Wziątek; Katarzyna Derwich (Frontiers Media S.A., 2022)
Brentuximab vedotin is a conjugate drug used mainly in Hodgkin lymphoma, systemic and primary cutaneous anaplastic large cell lymphomas, and CD30-expressing peripheral T-cell lymphoma. We report a unique case of acute pancreatitis associated with brentuximab vedotin in a 17-year-old male patient suffering from classical Hodgkin lymphoma. Diagnosed in 2020, the patient was classified to an intermediate therapeutic group and disease's grade was IIIAE. The patient was treated with brentuximab vedotin and bendamustine in the third line. Two weeks after the drug administration, the patient developed acute epigastric pain. Laboratory and radiological findings confirmed the clinical suspicion of acute pancreatitis that was managed with opioid pain medications, meropenem, parenteral nutrition, ondansetron and omeprazole. This is the first case report of brentuximab vedotin-associated acute pancreatitis in the pediatric patient reported in the literature to the best of our knowledge.